SUSPECTING HAEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS (HLH) IN PATIENTS WITH A HIGH FERRITIN - Syed Mujtaba Hasnain Nadir; Sheza Arif Toor; AbdulRahman Elbayouk; Moinuddin Mujeeb (Journal of Ayub Medical College Abbottabad, 2023)
Heamophagocytic Lymphohistiocytosis (HLH) is problematic to diagnose. The conditions that predispose to HLH present in a similar fashion, such as sepsis and haematological cancers. We look at the case of a 66-year-old man with a diagnosis of CLL, who presented with pyrexia and non-specific symptoms which included abdominal discomfort and weight loss. Sepsis, the principal suspicion was thoroughly investigated and excluded. Routine autoimmune pathologies were exhausted with comprehensive panels. The patient was trialled on steroids, presumptively, with a limited response. What was most peculiar in his blood tests was an unusually high Ferritin of > 50000. The parent clinical team was at a loss to explain the unusually high ferritin when a locum consultant suggested the diagnosis of Haemophagocytic Lymphohistiocytosis based on a similar presentation she had observed many years ago. The patient was started on pulsed Etoposide and Dexamethasone, however, unfortunately, he could not make a recovery.